Geotecnologias aplicadas ao zoneamento agroecológico do estado do Mato Grosso do Sul / Geotechnologies applied for Agroecological Zoning of the Mato Grosso do Sul State (Brazil) - Silvio Barge Bhering; Cesar Chagas da Silva; Waldir Carvalho Junior; Nilson Rendeiro Pereira; Fernando Cézar Saraiva Amaral; Maria José Zaroni; Alexandre Ortega Gonçalves (Revista Sociedade & Natureza, 2014)
This study aimed to present the methodological approach of the agroecological zoning of Mato Grosso do Sul State. The approach incorporated quantitative and qualitative assessment, with geotechnologies (satellite image–landsat 5, global positioning system, geographic information system, digital mapping, software of digital image processing) adoption to perform an integrated analysis of environmental data. Primary soils information associated with terrain attributes and climate characteristics were used with geotechnologies to evaluation of the natural erosion potential, natural fertility, internal drainage and moisture soil retention capacity of soil. The land use, and land cover and the environmental laws were observed. The integrated analysis of these data allowed environmental stratification in different agroecological zones. These zones are defined to agricultural use; pastures; conservation of natural resources or ecological restoration. In Bandeirantes case study, the agroecological zones recommended for agriculture sum 1,150 km2. The evaluation for conservation of natural resources and ecological results in 310 km2, and for the areas recommended for pastures sum 1,650 km2 or 53% of Bandeirantes municipality. This study allows conclude that the integrated analysis of environmental data with application of geotechnologies can subsidize a quantitative and qualitative assessment, stratifying the lands in different agroecological zones, each one with recommendations for sustainable use, and contributing as a powerful tool for spatial planning.